Groin sentinel node biopsy and 18F-FDG PET/CT-supported preoperative lymph node assessment in cN0 patients with vulvar cancer currently unfit for minimally invasive inguinal surgery: The GroSNaPET study. Issue 9 (September 2017) - Garganese, G.; Collarino, A.; Fragomeni, S.M.; Rufini, V.; Perotti, G.; Gentileschi, S.; Evangelista, M.T.; Ieria, F.P.; Zagaria, L.; Bove, S.; Giordano, A.; Scambia, G.
Abstract: Objective: The study aims were: 1) to verify the role of sentinel node biopsy (SNB) in a subset of patients with clinical N0 (cN0) invasive vulvar cancer (VC) who were still candidates for radical inguinal surgery according to the current guidelines; 2) to investigate whether a preoperative 18 F-FDG PET/CT (PET/CT) evaluation could improve the selection of node negative patients. Methods: From July 2013 to July 2016, all patients with VC admitted to our Division were evaluated by standard imaging and clinical exam. Among the patients assessed as cN0 we enrolled those unsuitable for SNB, due to: T > 4 cm, multifocal tumors, complete tumor diagnostic excision, contralateral nodal involvement and local recurrence. A preoperative PET/CT was performed. For each patient surgery included SNB, performed using a combined technique (radiotracer plus blue dye), followed by standard inguino-femoral lymphadenectomy. The reference standard was histopathology. Results: Forty-seven patients entered the study for a total of 73 groins. Histopathology revealed 12 metastatic SNs in 9 groins. No false negative SNs were found (NPV 100%). PET/CT showed a negative predictive value of 93%. Conclusions: Our data suggest that SNB is accurate and safe even in cN0 patients currently excluded from this procedure, providing that a careful preoperative selection is performed. PET/CT allows a reliable assessment of LN status and may be an effective support for the selection of patients who are safe candidates for SNB.